Angielskie zapożyczenia onomatopeiczne używane do opisu dźwięków wydawanych przez instrumenty perkusyjne - Taraszka-Drożdż, Barbara (Papers in Linguistics, 2020)
This article discusses onomatopoeic words borrowed from English that are used by contemporary Polish musicians to describe the sounds produced by percussion instruments.